Analisis Kerapatan dan Keanekaragaman Jenis Pohon di Universitas Jember Menggunakan Sistem Informasi Geografis - Andika Rahmat Hidayatulloh (Fakultas Ilmu Komputer, 2025)
Jember University is a green campus that has a Green Campus program as a form of environmental conservation. Efforts made in the form of green open space (RTH) management and conservation. The management requires data including the number and type of trees, area, density and others. This study focuses on data collection on the number, type, density and geographical location of trees. The method used is Vegetation Analysis to determine the number and density of trees, while for tree types using the Shannon Index Species Diversity. GIS is used to determine the area, geographical location and mapping. The results obtained in this study were 2,741 trees, 50 species, an area of 76 ha. The largest Relative Density value is 28.7% owned by mahogany trees, while the smallest value is 0.036% owned by several trees including mengkudu, baobab, juwet, karetan and jackfruit. The results of the Species Diversity value are 2.64 which is included in the moderate level. Based on the tree type data, it can be concluded that Jember University has several variations of plants and meets the Green Campus standards. Meanwhile, data on the number, density and area can be used as a reference for green open space management and conservation. Then the results of the analysis are made into a density and diversity map to describe the geographical location of trees and the Geographic Information System website as a publication and information media.
Entry oleh Arif 2026 Februari 10
Keywords: Green Campus; Vegetation Analysis; Species Diversity; GIS